2009
DOI: 10.1016/s0167-8140(12)72767-6
|View full text |Cite
|
Sign up to set email alerts
|

Imrt in Image-Guided Single Vocal Cord Irradiation

Abstract: Purpose: We have been developing an image-guided single vocal cord irradiation technique to treat patients with stage T1a glottic carcinoma. In the present study, we compared the dose coverage to the affected vocal cord and the dose delivered to the organs at risk using conventional, intensity-modulated radiotherapy (IMRT) coplanar, and IMRT non-coplanar techniques. Methods and Materials: For 10 patients, conventional treatment plans using two laterally opposed wedged 6-MV photon beams were calculated in XiO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…Targeting only the involved vocal cord with RT could further improve voice quality, and reduce the radiation exposure of the surrounding OAR. Osman et al (9)(10)(11)(12), Levendag et al (13) and Kwa et al (14) explored the technical feasibility, and dosimetric advantages, of targeting only a single affected vocal cord with IMRT for T1a glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting only the involved vocal cord with RT could further improve voice quality, and reduce the radiation exposure of the surrounding OAR. Osman et al (9)(10)(11)(12), Levendag et al (13) and Kwa et al (14) explored the technical feasibility, and dosimetric advantages, of targeting only a single affected vocal cord with IMRT for T1a glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few studies have investigated the possibility of changing the target volume. Only one institution in the Netherlands has investigated limiting the IMRT target volume to a single affected vocal cord for T1a glottic cancer (9)(10)(11)(12)(13)(14); their studies revealed that IMRT with a limited target volume was associated with a reduction in the irradiation of adjacent normal tissue. However, the oncological outcomes of limiting the target volume to a single vocal cord throughout the course of RT remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Single vocal cord irradiation by means of 4D-CT-based IMRT at least for T1a tumors seems to have the potential to spare the intact vocal cord and thus improve voice quality. 9 Introducing the voice handicap index questionnaire, a validated, easy-to-use tool, 25 would help to standardize assessment of voice quality. Given the comparable disease control after IMRT compared to conventional radiotherapy at lower toxicity rates and improved position verification with image guidance, we consider a further decrease in the target volume using 4D-CT for minimizing radiation-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In 2007, as a first step toward conformal dose distributions using multibeam intensitymodulated radiotherapy (IMRT), 5,6 we decided to define the clinical target volume (CTV) such that the high dose could be exclusively limited to the larynx. Further reduction of the CTV volume was envisaged, [7][8][9] if the first step proved to give equal efficacy and less toxicity than opposed wedged fields. [10][11][12] Hereby, we present the analysis of 5 years of IMRT for early-stage glottic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative paucity of data examining CVD after larynx RT, concerns have spurred investigation into the use of more targeted methods, such as carotid-sparing intensity modulated radiation therapy (IMRT), in an effort to mitigate potential excess CVD (8,(19)(20)(21)(22). Although SEER-Medicare data do not include RT dose, field size, or dosimetric data, care was taken to exclude patients with disease features that would typically warrant more comprehensive RT field design, such as patients with T3 tumors, nodal metastases, or supraglottic or subglottic primary locations.…”
Section: Discussionmentioning
confidence: 99%